2005
DOI: 10.1142/s0192415x05003405
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Electrical Conduction Properties Between Meridians and Non-meridians

Abstract: Therapy using the acupuncture meridian system is an important part of traditional Chinese medicine. The purpose of this study was to investigate the electrical conduction properties of the meridians. The current conduction and potential profiles were compared after switching the current direction in the Hegu (LI-4) and Quchi (LI- 11) meridians and over a non-acupuncture point 1 cm from Quchi (LI-11) in 20 healthy subjects. Both meridians demonstrated significantly higher conductivity between Hegu (LI-4) and Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 0 publications
0
22
0
2
Order By: Relevance
“…Evidence for meridians is not convincing although physiologic correlates have been reported, including electrical conductive properties [152,153] and intermuscular or intramuscular connective tissue planes [154]. Associations between acupuncture points and trigger points [155] and tendinomuscular and tendinofascial structures are tantalizing [156,157].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Evidence for meridians is not convincing although physiologic correlates have been reported, including electrical conductive properties [152,153] and intermuscular or intramuscular connective tissue planes [154]. Associations between acupuncture points and trigger points [155] and tendinomuscular and tendinofascial structures are tantalizing [156,157].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Previous studies have provided a variety of information regarding the physiological effects of acupuncture on animal and human bodies. Most of them have indicated that acupuncture is able to increase blood flow [1], and at the acupuncture points and meridians have a high electrical conductance [2,3]. A relationship has also been suggested that among those acupuncture points and meridians with connective tissue planes [4] and the perivascular space [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the existence of electrical properties associated with the meridians and have proposed hypotheses to explain this phenomenon (Ahn et al, 2005;Chen, 1996;Lee et al, 2005;Lu et al, 1999). Recently, Schlebusch et al (2005) reported evidence of the acupuncture meridian structure in the human body obtained from the application of a standard method of infrared thermography.…”
Section: Introductionmentioning
confidence: 99%